2010
DOI: 10.1007/s00128-010-0037-6
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Health Hazards in Women Beedi Rollers in Bihar, India

Abstract: We studied the health problems of 197 female beedi rollers in Patna, Bihar, India to ascertain the effects of beedi rolling on health. The study found that more than 70% of the beedi rollers suffered from eye, gastrointestinal and nervous problems while more than 50% of the respondents suffered from respiratory problems, mostly throat burning and cough. More than 75% of the respondents faced osteological problems. Total RBC, WBC and platelet counts of the beedi rollers were significantly lower in comparison to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…[7] The International Labor Organization cites ailments such as exacerbation of tuberculosis, asthma, anemia, giddiness, postural and eye problems, and gynaecological difficulties among beedi workers. [8] Our study also showed similar findings.…”
Section: Discussionmentioning
confidence: 99%
“…[7] The International Labor Organization cites ailments such as exacerbation of tuberculosis, asthma, anemia, giddiness, postural and eye problems, and gynaecological difficulties among beedi workers. [8] Our study also showed similar findings.…”
Section: Discussionmentioning
confidence: 99%
“…14 Low platelet counts were reported in gasoline filling workers, 15,16 and those exposed to gas flares 17 and benzene, 18 as well as beedi rollers. 19 Lead affects the blood coagulation actions through endothelial tissue injury, reduced nitric oxide, tissue plasminogen activator and an increased production of plasminogen activator inhibitor-1. 20 The chronic Pb intoxication of animals has reported higher levels of PLT, platelet distribution width (PDW) and MPV.…”
Section: Introductionmentioning
confidence: 99%
“…These workers suffered from respiratory, eye, osteological, dermatological and nervous problems. Yasmin et al (2010) reported that more than 70% of the beedi rollers suffered from eye, gastrointestinal and nervous problems while more than 50% of the respondents suffered from respiratory problems, mostly throat burning and cough. More than 75% of the respondents faced osteological problems.…”
Section: Resultsmentioning
confidence: 99%